2019
DOI: 10.2215/cjn.05560519
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for 1-Year Graft Loss After Kidney Transplantation

Abstract: Background and objectivesWith expansion of the pool of kidney grafts, through the use of higher-risk donors, and increased attention to donor management strategies, the 1-year graft survival rate is subject to change. It is, therefore, useful to elucidate 1-year graft survival rates by dissecting the characteristics of the low-risk and high-risk kidney transplant cases. The objective of our study was to evaluate factors purported to influence the risk of 1-year graft loss in kidney transplant recipients.Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 61 publications
(43 reference statements)
4
37
0
4
Order By: Relevance
“…A high degree of HLA incompatibility between donor and recipient has been shown to predispose to development of de novo donor‐specific HLA antibodies (DSAs) as well as to reactivation of preformed DSAs (Dreyer & de Fijter, 2020; Foroutan et al., 2019; Mohan et al., 2012). This may lead to antibody‐mediated rejection and subsequently impair long‐term allograft survival (Mehra & Baranwal, 2016; Slavcev, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A high degree of HLA incompatibility between donor and recipient has been shown to predispose to development of de novo donor‐specific HLA antibodies (DSAs) as well as to reactivation of preformed DSAs (Dreyer & de Fijter, 2020; Foroutan et al., 2019; Mohan et al., 2012). This may lead to antibody‐mediated rejection and subsequently impair long‐term allograft survival (Mehra & Baranwal, 2016; Slavcev, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…According to the data of liver transplantation from China Liver Transplant Registry (http://www.cltr.org/), 92.63% of the donated livers were procured from DD, with 76.01% 1‐year graft survival, which is a little lower than that from the living donors (1‐year, 82.53%) . A recent study in kidney transplantation also showed that DD is a risk factor for 1‐year graft loss, though the effect is small . However, another study showed that grafts from different donor types have similar graft survival rates .…”
Section: Live Donor or Deceased Donor?mentioning
confidence: 99%
“…38 A recent study in kidney transplantation also showed that DD is a risk factor for 1-year graft loss, though the effect is small. 39 However, another study showed that grafts from different donor types have similar graft survival rates. 40,41 If uterine graft survival is defined as graft survival past 12 months postoperatively, then the total graft survival rate was 67% (29/43) in the recipients reported up to date, including 71% (22/31) and 58% (7/12) from the living and DD, respectively.…”
Section: Hrt On Pod30mentioning
confidence: 99%
“…There are several risk factors for the formation of DSA and not surprisingly, non-adherence or lowering immunosuppressive drugs for clinical reasons play a crucial role (44)(45)(46)(47)(48). However, one can only form antibodies if there is a foreign HLA molecule and therefore the main risk factor is the degree of HLA mismatch between the recipient and the donor (49). Several studies show that HLA class II mismatch, in particular HLA-DQ, is most important (40,41,50).…”
Section: Donor Specific Antibodiesmentioning
confidence: 99%